2022
DOI: 10.1109/access.2022.3196471
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality as Support to the Learning Process of Forensic Scenarios

Abstract: Virtual Reality (VR) represents a computer technology to create a simulated threedimensional (3D) environment. Compared to the traditional user interfaces, VR places the user inside an experience. This research aimed to implement and examine modern learning strategies and activities with the VR for teaching crime scene investigation. The target group of this piloting study consisted of all students who enrolled in a crime scene investigation course at Al-Istiqlal University during the Spring semester of 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In fact, significantly higher levels of workload and completion times were recorded. Also, other studies reporting the use of Virtual Reality as a support in the training of forensic science and crime scene investigation showed that VR is a helpful tool for learning and practicing problem-solving skills [25,26]. As reported by Khalilia et al, [25] students had a positive experience with the collaboration strategies and activities during learning crime scene investigation using a virtual environment.…”
Section: Current Forensic Trainingmentioning
confidence: 80%
See 2 more Smart Citations
“…In fact, significantly higher levels of workload and completion times were recorded. Also, other studies reporting the use of Virtual Reality as a support in the training of forensic science and crime scene investigation showed that VR is a helpful tool for learning and practicing problem-solving skills [25,26]. As reported by Khalilia et al, [25] students had a positive experience with the collaboration strategies and activities during learning crime scene investigation using a virtual environment.…”
Section: Current Forensic Trainingmentioning
confidence: 80%
“…Currently, the most important applications of VR in forensic science is its use for training and education, and this is probably where the most upcoming development will be seen [21][22][23][24][25][26][27][28][29]. However, much work remains for it to become a standard training method and for it to gain acceptance on a broader scale.…”
Section: Current Forensic Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific literature shows that Virtual Reality (VR) is not new to forensic science. Previous studies examined the implementation of this technology as an instrument to support a variety of applications, including but not limited to witness interrogations (Sieberth et al 2019;Sieberth and Seckiner 2023), courtroom presentations (Ma et al 2010;Sevcik et al 2022;Sieberth et al 2021;Reichherzer et al 2022;Wang et al 2019), educational purposes (Kader et al 2020;Khalilia et al 2022;Jani and Johnson 2022;Drakou and Lanitis 2016), forensic examination of injuries (Koller et al 2019) and evidence (Guarnera et al 2022), and training of forensic practitioners (Mayne and Green 2020;Karabiyik et al 2019). However, much of the research has not considered virtual reality as an operational tool for forensic investigations.…”
Section: Related Workmentioning
confidence: 99%
“…In order to solve the problems of poor user experience and lack of navigational guidance in virtual simulation pedagogy, Dong et al 25 proposed a scheme for establishing an intelligent navigational chemical laboratory based on multimodal fusion. Khalilia et al 26 concluded that the learning process is supported through the implementation and study of modern learning strategies and activities for teaching crime scene investigation using virtual reality technology. An improved teaching mechanism empowered by edge computing–driven VR was proposed to enhance the education experience and improve the teaching environment 27 .…”
Section: Introductionmentioning
confidence: 99%